Phylotranscriptomics resolves phylogeny of the Heliozelidae (Adeloidea: Lepidoptera) and suggests a Late Cretaceous origin in Australia. (31st July 2019) - Milla, Liz; Moussalli, Adnan; Wilcox, Stephen A.; van Nieukerken, Erik J.; Young, David A.; Halsey, Mike; McConville, Thomas; Jones, Therésa M.; Kallies, Axel; Hilton, Douglas J.
Abstract: Heliozelidae are a cosmopolitan family of small, day‐flying moths, and include some pest species of commercial crops. Overall, the family is poorly known and lacks a well‐resolved phylogeny. Previous molecular and taxonomic work has revealed rich undescribed diversity within the family, particularly in Australia; however, the relationships amongst the major clades or genera were not resolved. We sequenced the transcriptomes of 39 taxa, representing all major genera of Heliozelidae, and seven outgroups representing most other Adeloidea families and the putative sister superfamily, Andesianoidea. The resulting phylogeny, based on the coding sequences of up to 1049 nuclear genes, provides a robust hypothesis for the generic relationships within Heliozelidae. On the basis of this analysis, the genus Plesiozela, previously proposed as sister group to all other Heliozelidae, is excluded from the family and formally transferred to Incurvariidae. By incorporating fossil and secondary time calibrations into our phylogeny, we estimated that Heliozelidae ancestors first appeared at the beginning of the Late Cretaceous, approximately 95 Ma. We propose an ancestral biogeographical range hypothesis of the family, based on a combination of our transcriptome data and a previous multigene study including over 100 species. Our ancestral range modelling results suggest that Heliozelidae are likely to have originated in the Australian region, with subsequent range expansions to the rest of the world. Abstract : We provide a robust, well‐resolved molecular phylogeny of the Heliozelidae (Adeloidea) family based on a phylogenomic‐level dataset derived from the transcriptomes of representative species. The relationships between the major Heliozelidae clades are resolved, including the placement of Plesiozela, considered sister to all other Heliozelidae, now formally transferred to Incurvariidae. The origin of the Heliozelidae family is estimated to the Late Cretaceous, pushing back earlier estimates. The ancestral range of the Heliozelidae is likely to have included the Australian region, with subsequent incursions into the rest of the world.